Physico-chemical and gel properties of agar from Gracilaria tenuistipitata from the lake of Songkhla, Thailand - Suthasinee Yarnpakdee (2018)
© 2015 Elsevier Ltd. Physico-chemical and gelling properties of agar extracted from Gracilaria tenuistipitata as affected by alkaline pretreatments using NaOH and KOH at various levels (3-7%, w/v) were investigated. Yield of native agar was 17.1%, whilst those of agars pretreated with NaOH and KOH ranged from 23.6% to 26.1%. Agar with alkaline pretreatment generally showed the better gelling property as evidenced by higher gel strength, gelling, melting temperatures and viscosity with coincidentally increased 3,6-anhydrogalactose (3,6-AG) content than did native agar. Additionally, native agar had a higher sulphate content with lower syneresis (P < 0.05) than those with alkaline pretreatment. Regardless of alkaline concentration, NaOH used for pretreatment rendered agar with a higher quality, compared with KOH. Agar (1.5%, w/v) pretreated with 5% NaOH exhibited the highest gel strength (482g/cm < sup > 2 < /sup > ) with high yield (25.3%). The decrease in total sulphate content and the increase in 3,6-AG content were observed in agar having 5% NaOH pretreatment as determined by FTIR spectroscopy. Finer and more compact network with smaller pores was visualised in gel from agar with 5% NaOH pretreatment. Therefore, the appropriate pretreatment by using 5% NaOH could increase yield and improve the gelling property of agar from G.tenuistipitata harvested from the lake of Songkhla, Thailand.